Hypoxia and Hypoxia-Inducible Factors in Leukemias - Deynoux, Margaux; Sunter, Nicola; Hérault, Olivier; Mazurier, Frédéric (Frontiers in Oncology, 2016)
Despite huge improvements in the treatment of leukaemia, the percentage of patients suffering relapse still remains significant. Relapse most often results from a small number of leukaemic stem cells (LSCs) within the bone marrow, which are able to self-renew and therefore re-establish the full tumour. The marrow microenvironment contributes considerably in supporting the protection and development of leukaemic cells. LSCs share specific niches with normal haematopoietic stem cells with the niche itself being composed of a variety of cell types including mesenchymal stem/stromal cells, bone cells, immune cells, neuronal cells and vascular cells. A hallmark of the haematopoietic niche is low oxygen partial pressure, indeed this hypoxia is necessary for the long-term maintenance of HSCs. Hypoxia is a strong signal, principally maintained by members of the hypoxia-inducible factor family. In solid tumours, it has been well-established that hypoxia triggers intrinsic metabolic changes and microenvironmental modifications, such as the stimulation of angiogenesis, through activation of HIFs. As leukaemia is not considered a “solid” tumour, the role of oxygen in the disease was presumed to be inconsequential and remained long overlooked. This view has now been revised since hypoxia has been shown to influence leukaemic cell proliferation, differentiation and resistance to chemotherapy. However, the role of HIF proteins remains controversial with HIFs being considered as either oncogenes or tumour suppressor genes, depending on the study and model. The purpose of this review is to highlight our knowledge of hypoxia and HIFs in leukaemic development and therapeutic resistance, and to discuss the recent hypoxia-based strategies proposed to eradicate leukaemias.